Teaching discourse markers in a technologically-enhanced language classroom - Abuczki, Ágnes; Parmaxi, Antigoni; Nicolaou, Anna (My University, 2018)
This paper reports on the methods and findings of a small-scale classroom research study focusing on the facilitation of the use of discourse markers (henceforth: DMs) by second language learners of English, at Cyprus University of Technology. In the framework of explicit teaching, mixed methods, combining traditional and digital tools, were employed in order to maximize the use of DMs in the EFL classroom. It was hypothesized that involvement in the lesson and the DM use of students along with the resulting coherence of their discourse is enhanced by and increases with the application of digital and interactive activities. In order to confirm or reject our hypothesis, an opinion questionnaire was administered to explore students’ perceptions about the use of digital and traditional tools demonstrated in class and to investigate the effectiveness of the enhancement of their skills in the use of discourse markers and in composing coherent texts and participating in collaborative interaction. Our study shows that students enjoy using digital tools, and, as a result of teaching and practice, they use more DMs; consequently, their pragmatic competence increases, and their interaction and argumentation becomes more natural and easier to follow.
Keywords: CALL; Digital tools; Discourse markers